2018
DOI: 10.1111/modl.12463
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Reorientations and L2 Interactional Settings: A Postscript to the Special Issue

Abstract: This postscript discusses the contributions of the four articles in this issue to the field and positions them in relation to other studies in recent CA research on L2. The articles focus on the two arenas for L2 learning: the classroom and the lifeworld of learners. These arenas are widely different from each other and equally so within with respect to organization and participation frameworks and the social practices deployed; but the interactional problems that participants confront inside and outside of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…But this approach also acknowledges with humility that the meaning of that which is visible may not be readily obvious to the analyst without painstaking piecing together other pieces of the mosaic. Although this diverges somewhat from the philosophical underpinnings of EMCA (but see Waring et al, 2012), we see this "third way" of researching as contributing just as vigorously to the larger project of revisiting psychological concepts in research on language learning and teaching from the praxeological perspective (Kasper & Wagner, 2018;Kubanyiova, 2019;Kubanyiova & Feryok, 2015).…”
Section: Towards a Third Way Of Researching L2 Wtcmentioning
confidence: 98%
“…But this approach also acknowledges with humility that the meaning of that which is visible may not be readily obvious to the analyst without painstaking piecing together other pieces of the mosaic. Although this diverges somewhat from the philosophical underpinnings of EMCA (but see Waring et al, 2012), we see this "third way" of researching as contributing just as vigorously to the larger project of revisiting psychological concepts in research on language learning and teaching from the praxeological perspective (Kasper & Wagner, 2018;Kubanyiova, 2019;Kubanyiova & Feryok, 2015).…”
Section: Towards a Third Way Of Researching L2 Wtcmentioning
confidence: 98%
“…Thus, applying CA as a method in research that aims to investigate longitudinal change in the learner's command of linguistic elements or skills over a longer period of time is not a self‐evident choice. Instead, following from CA's demand of grounding the analysis in an emic (i.e., the participants’) perspective, many CA–SLA studies have focused on the ways participants ‘do learning’ at the microlevel of interaction (see, for example, Brouwer, 2003; Gardner, 2012; Kasper & Wagner, 2018; Majlesi & Broth, 2012; and a recent overview by Jakonen, 2018). This idea was formulated by Gardner (2012), who stressed that while the actual moments of learning might be unreachable for analysts, detailed CA helps locate moments when participants orient to learning.…”
Section: Conversation Analysis For Second Language Acquisition Changmentioning
confidence: 99%
“…However, it should also be acknowledged that, while prior CA–SLA studies have repeatedly shown learning activities taking place in situations where understanding problems become visible and addressed through conversational repair (e.g., Hellermann, ; Lilja, ), the maintenance of understanding is neither conceptually nor empirically the same as learning. Indeed, as Kasper and Wagner () observe, the work of identifying and acting on learning objects involves an activity shift from “achieving intersubjectivity to doing learning” (p. 83). Moreover, learning can also be an activity that participants do for its own sake, such as when small children entertain themselves by learning to count in the L2 (Sahlström, ).…”
Section: Language Learning As a Temporal And Observable Members’ Phenmentioning
confidence: 99%
“…And as Kasper and Wagner (, p. 86) note, this is where learning interactions in CLIL classes and “institutional interaction in the wild” overlap.…”
mentioning
confidence: 98%